1991
DOI: 10.1017/s0033291700022418
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE) as a screening test for dementia

Abstract: SYNOPSISA 26-item informant questionnaire (IQCODE) and the Mini-Mental State Examination (MMSE) were compared as screening tests for dementia in a sample of 69 patients. Dementia diagnoses were made by both a clinician and a research interview using a computer algorithm to meet DSM-III-R and ICD-10 (Draft) criteria. The IQCODE was found to perform at least as well as the MMSE against all diagnoses and significantly better when judged against the algorithmic ICD-10 diagnoses. Also, the IQCODE was found to be un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
197
3
15

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 293 publications
(221 citation statements)
references
References 5 publications
6
197
3
15
Order By: Relevance
“…Functional assessment-Change in everyday behavior associated with cognitive decline was assessed using the IQCODE (Jorm et al, 1991;Jorm & Jacomb, 1989;Jorm & Korten, 1988). This is a 26-item interview-based questionnaire completed by an informant familiar with the participant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional assessment-Change in everyday behavior associated with cognitive decline was assessed using the IQCODE (Jorm et al, 1991;Jorm & Jacomb, 1989;Jorm & Korten, 1988). This is a 26-item interview-based questionnaire completed by an informant familiar with the participant.…”
Section: Methodsmentioning
confidence: 99%
“…Both the English and Spanish versions of the IQCODE have been published in their entirety elsewhere (Jorm, 1994;Morales et al, 1995). The IQCODE has been shown to have high internal consistency, with alphas ranging from .93 to .95 (Jorm & Jacomb, 1989) and good test-retest reliability, both over a few day period (r = .96) and over 1 year (r = .75) (Jorm & Jacomb, 1989;Jorm et al, 1991). The IQCODE also has limited association with education (Fuh et al, 1995;Jorm & Jacomb, 1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The IQCODE (Jorm and Korten, 1988;Jorm and Jacomb, 1989;Jorm et al, 1991) was used as a measure of functional change in the determination of clinical diagnosis. This is a 26-item interview-based questionnaire completed by an informant familiar with the participant.…”
Section: Instrumentsmentioning
confidence: 99%
“…The IQCODE has been shown to have high internal consistency, with alphas ranging from 0.93 to 0.95 (Jorm and Jacomb, 1989) and good test-retest reliability, both over a few day period (r =0.96) and over one year (r =0.75) (Jorm and Jacomb, 1989;Jorm et al, 1991). A number of studies have shown that it is a sensitive indicator of dementia (sensitivity =0.86 and specificity =0.80) (Jorm et al, 1991;.…”
Section: Instrumentsmentioning
confidence: 99%